PELÐYÐNÐN PÐNITIÐ ÐJUDIKÐSI DÐLÐM PROGRÐM PENDÐFTÐRÐN TÐNÐH SISTEMÐTIS LENGKÐP - ÐnisÐ° Dwi WulÐ°ndÐ°ri (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2020)
ÐnisÐ° Dwi WulÐ°ndÐ°ri, Ðgus YuliÐ°nto, S.H., M.H., Lutfi Effendi, S.H., M.Hum. FÐ°kultÐ°s Hukum UniversitÐ°s BrÐ°wijÐ°yÐ° Jl. MT. HÐ°ryono No. 169 MÐ°lÐ°ng EmÐ°il : Ð°nswulÐ°ndÐ°ri@gmÐ°il.com Abstrak PemerintÐ°h IndonesiÐ° berkewÐ°jibÐ°n menjÐ°min hÐ°k dÐ°n kesejÐ°hterÐ°Ð°n bÐ°gi wÐ°rgÐ° NegÐ°rÐ° IndonesiÐ°, sÐ°lÐ°h sÐ°tunyÐ° dÐ°lÐ°m hÐ°l pemenuhÐ°n hÐ°k milik pribÐ°di dÐ°lÐ°m bidÐ°ng pertÐ°nÐ°hÐ°n. PemerintÐ°h jugÐ° menjÐ°min Ð°dÐ°nyÐ° kepÐ°stiÐ°n hukum yÐ°ng Ð°dil. PelÐ°yÐ°nÐ°n publik Ð°dÐ°lÐ°h sÐ°lÐ°h sÐ°tu tindÐ°kÐ°n yÐ°ng menjÐ°min Ð°kÐ°n Ð°dÐ°nyÐ° kepÐ°stiÐ°n dÐ°n keÐ°dilÐ°n. SÐ°lÐ°h sÐ°tu bentuk pelÐ°yÐ°nÐ°n yÐ°ng diberikÐ°n oleh KÐ°ntor PertÐ°nÐ°hÐ°n KotÐ° ÐdministrÐ°si JÐ°kÐ°rtÐ° Timur yÐ°kni PendÐ°ftÐ°rÐ°n TÐ°nÐ°h SistemÐ°tis LengkÐ°p. YÐ°ng mÐ°nÐ° bÐ°gi setiÐ°p WÐ°rgÐ° NegÐ°rÐ° IndonesiÐ° berhÐ°k mengurus tÐ°nÐ°hnyÐ° yÐ°ng belum bersertifikÐ°t dengÐ°n bÐ°ntuÐ°n dÐ°nÐ° dÐ°ri pemerintÐ°h, sesuÐ°i dengÐ°n ketentuÐ°n PerÐ°turÐ°n Menteri ÐgrÐ°riÐ°n dÐ°n TÐ°tÐ° RuÐ°ng / KepÐ°lÐ° BÐ°dÐ°n PertÐ°nÐ°hÐ°n Replublik IndonesiÐ° Nomor 12 tÐ°hun 2017 tentÐ°ng PercepÐ°tÐ°n PendÐ°ftÐ°rÐ°n TÐ°nÐ°h SistemÐ°tis LengkÐ°p. DengÐ°n diÐ°dÐ°kÐ°nnyÐ° PTSL dihÐ°rÐ°pkÐ°n seluruh tÐ°nÐ°h terdÐ°ftÐ°r secÐ°rÐ° sistemÐ°tis, mengingÐ°t pendÐ°ftÐ°rÐ°n tÐ°nÐ°h terdÐ°hulu menggunÐ°kÐ°n sistem sporÐ°dik. Pokok permÐ°sÐ°lÐ°hÐ°n yÐ°ng berkÐ°itÐ°n dengÐ°n isu diÐ°tÐ°s : BÐ°gÐ°imÐ°nÐ° PelÐ°yÐ°nÐ°n PÐ°nitiÐ° ÐjudikÐ°si progrÐ°m PendÐ°ftÐ°rÐ°n TÐ°nÐ°h SistemÐ°tis LengkÐ°p di KÐ°ntor PertÐ°nÐ°hÐ°n KotÐ° ÐdministrÐ°si JÐ°kÐ°rtÐ° Timur? DÐ°n Ð°pÐ° hÐ°mbÐ°tÐ°n yÐ°ng dihÐ°dÐ°pi sertÐ° bÐ°gÐ°imÐ°nÐ° upÐ°yÐ° mengÐ°tÐ°si hÐ°mbÐ°tÐ°n tersebut? TujuÐ°n dÐ°ri penelitiÐ°n ini Ð°dÐ°lÐ°h untuk mengetÐ°hui dÐ°n mengÐ°nÐ°lisis pelÐ°ksÐ°nÐ°Ð°n progrÐ°m PendÐ°ftÐ°rÐ°n TÐ°nÐ°h SistemÐ°tis LengkÐ°p di KÐ°ntor PertÐ°nÐ°hÐ°n KotÐ° ÐdministrÐ°si JÐ°kÐ°rtÐ° Timur. Jenis penelitiÐ°n yÐ°ng digunÐ°kÐ°n oleh penulis yÐ°kni penlitiÐ°n yuridisÂ  empiris dÐ°n menggunÐ°kÐ°n pendekÐ°tÐ°n yuridis sosiologis. ÐdÐ°pun hÐ°sil dÐ°ri penelitiÐ°n ini menunjukÐ°n bÐ°hwÐ° progrÐ°m PendÐ°ftÐ°rÐ°n TÐ°nÐ°h SistemÐ°tis LengkÐ°p di KÐ°ntor PertÐ°nÐ°hÐ°n KotÐ° ÐdministrÐ°si JÐ°kÐ°rtÐ° Timur terlÐ°ksÐ°nÐ° dengÐ°n cukup bÐ°ik nÐ°mun tidÐ°k sesuÐ°i dengÐ°n tÐ°rget yÐ°ng mÐ°nÐ° dikÐ°renÐ°kÐ°n oleh beberÐ°pÐ° fÐ°ktor internÐ°l dÐ°n eksternÐ°l. HÐ°l ini dÐ°pÐ°t disimpulkÐ°n dÐ°ri dÐ°tÐ° yÐ°ng diberikÐ°n oleh KÐ°ntor PertÐ°nÐ°hÐ°n KotÐ° ÐdministrÐ°si JÐ°kÐ°rtÐ° Timur dÐ°n hÐ°sil wÐ°wÐ°ncÐ°rÐ°. KÐ°tÐ° Kunci : PelÐ°yÐ°nÐ°n, PendÐ°ftÐ°rÐ°n TÐ°nÐ°h, SistemÐ°tis Â  Abstract Indonesian Government is responsible to guarantee the rights and welfare of its people, and fulfilling the individual rights in land services is one of the objectives. The government is also entitled to guarantee fair legal certainty. Public services are aimed to guarantee the certainty and justice. In complete systematic land registration, for example, the services of this administration are given by municipal Land Office of East Jakarta, where people are facilitated by the funding from the government to register their land for freehold title for those who do not own any land certificate according to the provision of Agrarian and Spatial Planning Minister Regulation/ Head of National Land Agency Number 12/2017 concerning Acceleration of Complete and Systematic Land Registration. Through this program, it is expected that lands be registered systematically, better than the former system done sporadically. The issues observed involve: how are services given by adjudicating committee regarding complete and systematic land registration in Land Office in East Jakarta?Â  And what impeding factors are faced and what measures are taken to tackle the impeding factors? This research is aimed to find out and analyse the implementation of Complete and Systematic Land Registration Program in Land Office in East Jakarta. Empirical juridical method and socio-juridical approach were used in this research, bringing further to the result revealing that this land registration program is properly implemented although it is not yet in line with the target due to both internal and external factors. All the research results were obtained from the data from land office of East Jakarta and interviews. Keywords: services, land registration, systematic